UTILIZATION OF 'AQUAJAYA X AQUARISET' YOUTUBE ACCOUNT AS A MEANS OF EDUCATING AQUASCAPER - Bimo Berdiarto Jokoniko; Megawati Megawati; Aditya Winarto (INJECT (Interdisciplinary Journal of Communication), 2023)
This research starts from the phenomenon of technology that causes the dependence of human activities on the internet in life. Technological advances make it easier for people to find and get the desired information and entertainment through social media. One of the many people explore the hobby is Aquascape. So, researchers researched how AquaJaya x AquaRiset uses YouTube as a means of education. The main purpose of this research is to find out specifically the use of YouTube as educational advice for aquascape using social information processing theory. This research uses a descriptive qualitative method with semi-structured interviews with a content owner of the AquaJaya x AquaRiset YouTube account, and three viewers and subscribers of the account. The AquaJaya x AquaRiset YouTube account is proven to apply the values of social information processing theory and provide education to aquascapes.